Safety and Efficacy of Bipolar vs Monopolar Transurethral Resection of Bladder Tumor- A Randomized Controlled Trial (Nepal Medical College Journal, 2020)
Monopolar Transurethral resection of bladder tumor (TURBT) has been a gold standard for bladder tumor. Initial studies of bipolar TURBT were promising, however, no high level evidence exists and its exact role remains undefined. We compared the safety and efficacy of bipolar and monopolar TURBT. Primary objective was to compare the incidence of obturator jerk. The secondary objectives included the comparison of decrease in hemoglobin, recoagulation and transfusion requirements, bladder perforation, decrease in sodium, resection syndrome and resection time, hospital stay, detrusor muscle identification and severe cautery artifact in resected specimen in two groups. A randomized control trial was conducted for one year. All patients undergoing TURBT for suspected bladder tumors were eligible. Patient’s refusal to participate, unfitness for spinal anesthesia and lack of tumor in lateral wall were excluded. Of the 118 TURBT done during study period, 48 were excluded and 70 patients, 36 in monopolar and 34 in bipolar arms, were analyzed. The incidence of obturator jerk was less in bipolar arm but not significantly different (26.4% vs. 47.2%, p=0.073). There was no significance difference in most of the secondary outcomes except lesser hemoglobin drop (0.49gm/dl vs. 0.98gm/dl, p=0.016) and lesser resection time in bipolar arm (33.0 mins vs. 46.8mins, p=0.008). Bipolar was not different to monopolar TURBT with respect obturator jerk and most of the secondary outcomes. However, with bipolar TURBT, there was significantly less resection time and although hemoglobin drop was less as well, it was not clinically significant.